HOW THE ISLAMIC PERSPECTIVE LOOKS AT ECONOMIC ACTIVITY FROM A CAPITALIST POINT OF VIEW - Rava Fernanda Purnama; Fereshti Nurdiana Dihan; Putri Dwi Cahyani; Rasinah Rasinah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Looking at current conditions, no one can argue that the entry of the digital era is closely related to the dominance of the capitalist regime. The end of the Cold War is often seen as the victory of capitalism because it was followed by the fall of communism-socialism, the Soviet Union, and its satellite states. The logic and culture of capitalism permeate and influence almost every aspect of modern life (Heriyanto, 2000). Kelen (Winarso, 2020) agrees, arguing that capitalism is the most widely accepted economic system in the world. Due to globalization, a free market economic system based on capitalism has emerged as the standard by which most countries judge their own economic policies. What gives? Since no country can avoid the impact of economic globalization, and since the supply of natural resources varies from country to country, it is unrealistic to expect one country to be able to provide its citizens with everything they need in a limited sense. Indonesia is no exception to the rule that globalization and capitalism, the two pillars of the global economic system, are inextricably linked and give birth to a distinctive state of the world economy that in turn impacts the fabric of society everywhere. The history, philosophy, and most influential philosophies in management from both a capitalist and Islamic perspective will be discussed here.